Improved electrode positions for local impedance measurements in the lung—a simulation study. (4th November 2016) - Orschulik, Jakob; Petkau, Rudolf; Wartzek, Tobias; Hochhausen, Nadine; Czaplik, Michael; Leonhardt, Steffen; Teichmann, Daniel
Abstract: Impedance spectroscopy can be used to analyze the dielectric properties of various materials. In the biomedical domain, it is used as bioimpedance spectroscopy (BIS) to analyze the composition of body tissue. Being a non-invasive, real-time capable technique, it is a promising modality, especially in the field of lung monitoring. Unfortunately, up to now, BIS does not provide any regional lung information as the electrodes are usually placed in hand-to-hand or transthoracic configurations. Even though transthoracic electrode configurations are in general capable of monitoring the lung, no focusing to specific regions is achieved. In order to resolve this issue, we use a finite element model (FEM) of the human body to study the effect of different electrode configurations on measured BIS data. We present evaluation results and show suitable electrode configurations for eight lung regions. We show that, using these optimized configurations, BIS measurements can be focused to desired regions allowing local lung analysis.